2017
DOI: 10.1111/php.12749
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Chemoprevention: Current Status and Future Prospects

Abstract: The incidence of skin cancers, both non-melanoma as well as melanoma, are increasing in the United States. The ultraviolet radiation, mainly from sun, is considered the major cause for these neoplasms. While non-melanoma skin cancers are far more numerous, melanoma remains the most challenging. This is because melanoma can become extremely aggressive and its incidence is increasing worldwide due to lack of effective early detection, as well as disease recurrence, following both surgery and chemotherapy. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 199 publications
(244 reference statements)
0
37
0
5
Order By: Relevance
“…Exposure to vitamin A activates the nuclear retinoid receptors RAR and RXR (reviewed in Chhabra et al 40 ). Pre-clinical studies of vitamin A and its precursors (retinol and the carotenoid pro-vitamins for vitamin A including beta-carotene) for melanoma chemoprevention have found both growth inhibiting and growth promoting effects on human cell lines.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Exposure to vitamin A activates the nuclear retinoid receptors RAR and RXR (reviewed in Chhabra et al 40 ). Pre-clinical studies of vitamin A and its precursors (retinol and the carotenoid pro-vitamins for vitamin A including beta-carotene) for melanoma chemoprevention have found both growth inhibiting and growth promoting effects on human cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the observed effects are thought to be mediated by the strong antioxidant properties of vitamin E and its ability to quench free radicals and inhibit lipid peroxidation (reviewed in Chhabra et al 40 ). Recent data, however, have shown that Trolox, a vitamin E analog, increased migration and invasion in human melanoma cell lines through effects on the glutathione system 57 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although 95% of UVB radiation is absorbed in the protective ozone layer in our outer environment, the remaining 5% inbound UVB is a potent genotoxic agent to impart considerable response in skin cells, including melanocytes. UVB penetrates as deep as the epidermal basal cell layer of the skin and induces DNA damage , particularly in the form of cyclobutane pyrimidine dimers (CPDs), which are an important source of mutations in UV‐induced melanoma . On the other hand, UVA is a potent driver of oxidative DNA damage in skin cells and can cause mutations by generating reactive oxygen species (ROS) that oxidize guanine at the 8th position to produce 8‐hydroxy‐2′‐deoxyguanosine (8oxoG) .…”
Section: Introductionmentioning
confidence: 99%